Pulp analysis of teeth submitted to different types of forces: a histological study in rats - Cuoghi, Osmar Aparecido [UNESP]; Faria, Lorraine Perciliano de; Ervolino, Edilson [UNESP]; Barioni, Sônia Regina Panzarini [UNESP]; Topolski, Francielle [UNESP]; Arana-Chavez, Victor Elias; Mendonça, Marcos Rogério de [UNESP] (Univ Sao Paulo Fac Odontologia Bauru, 2018)
Objective: The purpose of this study was to histologically evaluate pulp and dentin under induced tooth movement (ITM) with different types of forces. Material and Methods: The maxillary right first molars of rats were submitted to movement with continuous (CF), continuous interrupted (CIF) and intermittent (IF) forces during 5, 7 and 9 days with nickel-titanium (NiTi) closed-coil springs exerting 50cN force magnitude. The groups were histologically evaluated as for cellularity pattern, presence of dystrophic, hemodynamic alterations in the pulp as well dentin alterations. The main observed alterations were related to hemodynamic pulp characteristics, such as presence of thrombosis, vascular congestion and hemorrhages. The hemodynamic alterations were statistically evaluated by Shapiro-Wilk normality test and analysis of variance by the Kruskall-Wallis test. Results: There was no significant differences observed between groups in the different types of applied forces and duration of ITM (vascular congestion, p=1.000; hemorrhage, p=0.305; thrombosis, p=1.000). Conclusions: Pulp tissue alterations resulting from ITM were limited to hemodynamic events, without progressing to irreversible degeneration, regardless of the type of force applied.
Keywords: Tooth movement; Dental pulp; Histology